Impact of retinitis pigmentosa on daily and social life - Del Álamo Martín, María Teresa; Álvarez López, Isabel; R. Coca, Juan (Cuadernos de Trabajo Social, 2022)
Retinal dystrophies cause progressive degeneration of the retina in people who suffer from them, leading to loss of vision over the years, negatively affecting their functional capacity and social participation. The research used a mixed methodology with a CUAN+CUAL design. The quantitative part was a case-control study with a non-probabilistic, purposive sample of 30 people with and without retinitis pigmentosa matched by age and sex. All of them were administered the World Health Organization Model Disability Survey, Short Version (MDSc). External factors, which may influence everyday health-related problems, family and social support and attitudes of others, were compared. The qualitative part consisted of the analysis of data obtained through in-depth interviews with the 15 people with retinitis pigmentosa in the case group. Significant differences were obtained between the groups, showing greater difficulties of people with dystrophies in their daily life than those without, such as mobility, carrying out household tasks or social participation. Noise, brightness, lack of technological means to facilitate accessibility and the existing ocularcentrism in society, in addition to causing discomfort and nervousness, are a source of social exclusion. The results provide evidence that will enable social workers to intervene to promote the social participation of a group affected by a rare eye disease, avoiding inequalities and advancing their rights.